Uji Parameter Fisika Dan Kimia Untuk Menentukan Kualitas Air Hujan Yang Di Tampung Sebagai Kebutuhan Air Bersih: Uji parameter fisika dan kimia - K. Seme, Alan; A. Wulandari, Annisa; Marasabessy, Dzulfikar; R. Kumune, Robert (Casuarina: Jurnal Teknik Lingkungan, 2024)
This practicum aims to test the quality of rainwater in storage tanks that are used as clean water. The method used is a descriptive method to analyze three rainwater samples, taken from three different times, namely morning, afternoon and evening. The parameters measured are the degree of acidity (pH), total dissolved particles (TDS), salt content/salinity and electrical conductivity (DHL). The results of this research found that rainwater samples met water quality standards. Rainwater samples have an average pH value of 7.2 and an average salinity value of 3.6, however the TDS and DHL values in the water samples have a constant value of 0. The quality ofrainwater in the storage tank is of good quality to be used as clean water